2009
DOI: 10.1525/bio.2009.59.11.10
|View full text |Cite
|
Sign up to set email alerts
|

To Name or Not to Name: The Effect of Changing Author Gender on Peer Review

Abstract: The peer review model is one of the most important tools used in science to assess the relative merit of research. We manipulated a published article to reflect one of the following four author designations: female, male, initial, and no name provided. This article was then reviewed by referees of both genders at various stages of scientific training. Name changing did not influence acceptance rates or quality ratings. Undergraduate referees were less critical than graduate students or postdoctoral researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 21 publications
4
65
3
3
Order By: Relevance
“…Further, this behavior was most closely associated with major revisions, which suggests that reviewer self-citing serves a clarifying purpose, allowing reviewers to highlight inaccuracies in the representation of their work in the manuscript under review. No difference was found between male and female reviewers in regards to reviewer self-citations (RQ7), despite differences in male and female reviewing found in other studies of peer review (e.g., Wing Borsuk et al 2009;Lane and Linden 2009;Jayasinghe et al 2003). Furthermore, this confirms previous studies that have shown no difference in male and female rates of self-citation in journal articles (e.g., Symonds et al 2006;Borrego et al 2010).…”
Section: Discussionmentioning
confidence: 55%
“…Further, this behavior was most closely associated with major revisions, which suggests that reviewer self-citing serves a clarifying purpose, allowing reviewers to highlight inaccuracies in the representation of their work in the manuscript under review. No difference was found between male and female reviewers in regards to reviewer self-citations (RQ7), despite differences in male and female reviewing found in other studies of peer review (e.g., Wing Borsuk et al 2009;Lane and Linden 2009;Jayasinghe et al 2003). Furthermore, this confirms previous studies that have shown no difference in male and female rates of self-citation in journal articles (e.g., Symonds et al 2006;Borrego et al 2010).…”
Section: Discussionmentioning
confidence: 55%
“…Budden and her colleagues published several analyses of gender bias in manuscript reviewing by undergraduates, graduate students, postdocs, and journal reviewers (6,(17)(18)(19). In one, they analyzed journal acceptance rates for manuscripts submitted by women to Behavioral Ecology after it began blind peer review (18).…”
Section: Discrimination Against Women In Journal Reviewingmentioning
confidence: 99%
“…23, p. 350). In another study by Budden and her colleagues (17), 989 raters (undergraduates to postdocs) were given an identical manuscript with either no name, author's first initial only, a male name, or a female name. This study also found no sex discrimination.…”
Section: Discrimination Against Women In Journal Reviewingmentioning
confidence: 99%
“…50 In the same issue, however, Budden et al respond to Webb's critique, reasserting the validity of their conclusion that doubleblind reviews would foster gender equity for women. 51 Borsuk et al, in a study in which they contrived the byline of a published article to reflect either female, male, or no gender 52 and distributed it to undergraduate, graduate students, postdoctoral fellows, and faculty to assess any differences in their rejection rates. They found no evidence for differences based on author gender or evidence for same-gender preferences.…”
Section: Atkinson Notes That Many Authors Will 'Peddle Their Work' Unmentioning
confidence: 99%